Phylogenetics and Mitogenome Organisation in Black Corals (Anthozoa: Hexacorallia: Antipatharia): An Order-Wide Survey Inferred From Complete Mitochondrial Genomes - Barrett, Nick J.; Hogan, Raissa I.; Allcock, A. Louise; Molodtsova, Tina; Hopkins, Kevin; Wheeler, Andrew J.; Yesson, Chris (Frontiers in Marine Science, 2020)
Black corals (Anthozoa: Antipatharia) are an ecologically and culturally important group of deep-sea cnidarians. However, as the majority of species inhabit depths >50 m, they are relatively understudied. The inaccessibility of well-preserved tissue for species of interest has limited the scope of molecular analysis, and as a result only a small number of antipatharian mitochondrial genomes have been published. Using next generation sequencing, eighteen complete and five partial antipatharian mitochondrial genomes were assembled, increasing the number of complete mitochondrial genomes to twenty-two. This includes species from six antipatharian families, four of which were previously unrepresented, enabling the first family-level, full mitochondrial gene analysis over the whole order. The circular mitogenomes ranged in size from 17681 to 21669 bp with the large range in size due to the addition of an intron in COX1 in some species and size variation of intergenic regions. All mitogenomes contained the genes standard to all hexacoral mitogenomes (13 protein coding genes, two rRNAs and two tRNAs). The only difference in gene content is the presence of the COX1 intron in five families. The most variable mitochondrial gene is ND4 which may have implications for future barcoding studies. Phylogenetic analysis confirms that Leiopathidae is sister to all other families. Families Antipathidae, Cladopathidae and Schizopathidae are polyphyletic, supporting previous studies that call for a taxonomic revision.